Evaluating the performance of teachers of natural geography lessons in the high schools in the view of educational supervisors and school administrators (Raparin Journal of Humanities (RJH), 2023)
The aim of this study is to evaluate the performance of teachers of natural geography lessons in high schools in central Sulaymaniyah from the perspective of supervisors and managers for the year (2020-2021) based on the descriptive and analytical methods. The research community consists of all directors and education supervisors in both eastern and western educations، the study's sample of which is (47) participants. In order to collect data, the content of the closed survey form was 23 items in two scientific topics and 30 items in education, which totaled 53 items. After extracting the reliability of the scale by experts، its stability was also taken out based on the Pearson formula. Then، by applying survey upon the research sample and analyzing the collected data using tests such as (Two Way Annova without Replication، apporiate mean، weight percent) some important results were presented using the (SPSS). One of the most important results is that there is a difference between teachers' performance in terms of science and education in a way that the scientific aspects are weaker than the educational aspects، and there is no difference between supervisors and managers in their view of teachers' performance according to their level and years of experiencesgiving that the (P-value (5. 28) > 0. 05). Opening special courses، seminars and workshops are considered the best steps to eliminate teachers' scientific and educational weaknesses.